Building The Character of Indonesia's Sharia-Based Indonesian Human Resources As An Important Component In Dealing With The Asean Economic Community (MEA) - Alfi Amalia; Lubis, Andrew Satria (TALENTA Publisher, Universitas Sumatera Utara, 2021)
This study aims to analyze the character of Indonesia's sharia-based Indonesian human resources in the face of the Asean Economic Community (MEA). The data used is qualitative data, which is data collected from literature and other supporting sources. The approach used is qualitative approach using an in-depth approach to literature studies on aspects of Indonesian human resources based on sharia and MEA. The interesting thing about the findings is the internalization of strengthening tawhid (tawhid) as the main foundation for all practitioners / observers / economic communities consisting of: 1. Traders or entrepreneurs 2.Modal owner 3.Konsumen 4.Buruh.Furthermore, sharia competence and culture strongly support the process of building habits among all parties involved including the government as policy makers; especially those who support the realization of MEA as expected. In addition, the government also acts as a party that recommends rules and regulations. This research is relevant to explain how to build the character of Indonesia's sharia-based Indonesian human resources in dealing with the Asean Economic Community (MEA) in ASEAN. The new thing from this research is the internalization of strengthening tawhid (tawhid) as the main foundation for all practitioners / observers / economic communities consisting of 1). Traders or entrepreneurs 2). Owner capital 3). Consumer 4). Workers in Indonesian society.